2011
DOI: 10.1161/strokeaha.111.627265
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Vulnerability

Abstract: Background and Purpose-Rupture of atherosclerotic plaques is one of the main causes of ischemic strokes. The aim of this study was to investigate carotid plaque vulnerability markers in relation to blood flow direction and the mechanisms leading to plaque rupture at the upstream side of carotid stenoses. Methods-Frequency and location of rupture, endothelial erosion, neovascularization, and hemorrhage were determined in longitudinal sections of 80 human carotid specimens. Plaques were immunohistochemically ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 41 publications
4
48
1
Order By: Relevance
“…Because the cap stress, which is a potential physical factor that contributes to plaque rupture, increased as the asymmetry increased, we suspect that asymmetric plaque geometry could increase the danger of plaque rupture. This observation also agreed with clinical findings that upstream ruptured plaques exhibited a strongly pronounced longitudinal asymmetry (Cicha et al, 2011 Fig. 4 Equivalent stress contour in the longitudinal cross section at peak pressure (the arrow head denotes max stress location).The maximum cap stress increased as the asymmetry increased, and the location of it moved to the proximal cap for the asymmetric models.…”
Section: Resultssupporting
confidence: 86%
“…Because the cap stress, which is a potential physical factor that contributes to plaque rupture, increased as the asymmetry increased, we suspect that asymmetric plaque geometry could increase the danger of plaque rupture. This observation also agreed with clinical findings that upstream ruptured plaques exhibited a strongly pronounced longitudinal asymmetry (Cicha et al, 2011 Fig. 4 Equivalent stress contour in the longitudinal cross section at peak pressure (the arrow head denotes max stress location).The maximum cap stress increased as the asymmetry increased, and the location of it moved to the proximal cap for the asymmetric models.…”
Section: Resultssupporting
confidence: 86%
“…This finding suggests that the distribution of vessel density toward upstream regions is not just a feature exclusive for more advanced, late stage plaques. Ruptures in atherosclerotic plaques are most commonly found in the upstream region[47] and previous cross-sectional studies reported increased contrast agent uptake in carotid plaques from patients with previous ischemic stroke[15, 22, 24, 25]. In the current study, the distribution of contrast agent uptake between upstream and downstream parts of the plaque in patients with previous ipsilateral symptoms compared with asymptomatic patients was similar.…”
Section: Discussionsupporting
confidence: 71%
“…Different types of shear stress might induce different gene expression patterns in endothelial cells[2], possibly leading to differences in plaque phenotype. In fact, our group and others have shown that the upstream region of the advanced carotid plaque exhibits a more vulnerable phenotype and is often the site of plaque rupture[37]. Vascularization of the plaque has been linked to plaque vulnerability and progression, possibly by providing an entry point for inflammatory cells, causing intra-plaque hemorrhage (IPH), inflammation and subsequent destabilization[810].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrous cap of a plaque is exposed to the highest strain, and shear stress, at its upstream edge (49). Previous work has shown that macrophage invasion is higher in the upstream edge of plaques (24, 36) and that resident macrophages in the upstream edge increase expression of proteolytic enzymes (24), thereby weakening the plaque. In addition, the fibrous cap on the upstream edge of plaques tends to be more ulcerated and thinner and, when combined with high shear stresses, may lead to destabilization and rupture of the plaque (33, 49).…”
Section: Discussionmentioning
confidence: 99%